2021
DOI: 10.1111/jgh.15593
|View full text |Cite
|
Sign up to set email alerts
|

Tumor burden score as a new prognostic marker for patients with hepatocellular carcinoma undergoing transarterial chemoembolization

Abstract: Background and Aim Size and number are major determinants of tumor burden in hepatocellular carcinoma (HCC). Patients with HCC undergoing transarterial chemoembolization (TACE) have variable outcomes due to heterogeneity of tumor burden. Recently, tumor burden score (TBS) was proposed to evaluate the extent of tumor involvement. However, the prognostic accuracy of TBS has not been well evaluated in HCC. This study aimed to assess its prognostic role in HCC patients undergoing TACE. Methods A total of 935 treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 31 publications
5
24
1
Order By: Relevance
“…Tumor burden score (TBS), a new metric based on tumor size and tumor number, was firstly proposed for patients with colorectal liver metastases in 2017 ( 11 ). Recently, studies demonstrated that TBS also showed promising utility in stratifying prognosis of patients with hepatocellular carcinoma who underwent hepatectomy or liver transplantation ( 12 14 ). However, whether the prognosis of ICC patients could be dictated by TBS remained unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor burden score (TBS), a new metric based on tumor size and tumor number, was firstly proposed for patients with colorectal liver metastases in 2017 ( 11 ). Recently, studies demonstrated that TBS also showed promising utility in stratifying prognosis of patients with hepatocellular carcinoma who underwent hepatectomy or liver transplantation ( 12 14 ). However, whether the prognosis of ICC patients could be dictated by TBS remained unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Ho et al. promoted the TBS as a novel tumor burden-related scoring system and a new prognostic marker for patients with HCC undergoing TACE ( 19 ). The TBS was originally developed in patients with colorectal liver metastasis undergoing resections ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…For patients undergoing TACE, Ho et al. showed that the TBS could accurately discriminate risk stratifications for OS ( 19 ). However, subgroup analyses on patients within different BCLC stages and ALBI grades showed considerable overlap in the survival curves.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations